The protective effects of honey propolis on oxidative in kainic acid mediated excitotoxicity in rat brain - Wan Azman, Wan Norlina (2015)
Introduction : Propolis has been proposed to be protective on neurodegenerative disorders. It has been shown to have broad biological activities, which are principally attributed to the presence of flavonoids and caffeic acid phenyl ester (CAPE). Objective : To understand the neuroprotective effects of honeybee propolis, glutamine synthetase (GS) activity, nitric oxide (NO), thiobarbituric acid reactive substances (TBARS) and total antioxidant status (TAS) are studies in different brain regions- cerebral cortex (CC), cerebellum (CB) and brain stem (BS) of rats supplemented with propolis and subjected to kainic acid (KA) mediated excitotoxicity. Materials and method : Twenty four Sprague Dawley male rats weighing 250-300 grams were used as subjects in this study. The animals were divided into four groups with 6 rats in each group. Group 1; control, group 2 ; kainic acid treated, group 3 ; propolis treated and group 4 ; kainic acid and propolis treated . The animals were sacrificed at the specific time and decapitated using the guillotine and brains were quickly removed and the different brain regions, namely cerebral cortex (CC), cerebellum (CB) and brain stem (BS) were separated quickly and were used to prepare the homogenates for the assay of biochemical parameters. Results were analyzed by one-way ANOVA using SPSS software version 20. Conclusion :The results of this study clearly demonstrated the restoration of GS activity and NO levels in kainic acid mediated excitotoxicity. TBARS which is the marker of oxidative stress was increased significantly in all the three brain regions tested in KA group, but the increase of TBARS concentration by KA was prevented by prior supplementation with propolis and the concentration of TAS was decreased significantly in KA group compared to propolis and KA group indicating the depletion of TAS concentration by KA was prevented by supplementation of propolis. Hence, propolis can be a possible potential candidate of protective agent against excitotoxicity and neurodegenerative disorders.